Mr.Vc: a database of microarray and RNA-seq of Vibrio cholerae. (24th June 2019) - Zhang, Zhiyuan; Chen, Guozhong; Hu, Jun; Hussain, Wajid; Fan, Fenxia; Yang, Yalin; Zhou, Zhigang; Fang, Xiaodong; Zhu, Jun; Chen, Wei-Hua; Liu, Zhi
Abstract: Gram-negative bacterium Vibrio cholerae is the causative agent of cholera, a life-threatening diarrheal disease. During its infectious cycle, V. cholerae routinely switches niches between aquatic environment and host gastrointestinal tract, in which V. cholerae modulates its transcriptome pattern accordingly for better survival and proliferation. A comprehensive resource for V. cholerae transcriptome will be helpful for cholera research, including prevention, diagnosis and intervention strategies. In this study, we constructed a microarray and RNA-seq database of V. cholerae (Mr.Vc), containing gene transcriptional expression data of 145 experimental conditions of V. cholerae from various sources, covering 25 937 entries of differentially expressed genes. In addition, we collected relevant information including gene annotation, operons they may belong to and possible interaction partners of their protein products. With Mr.Vc, users can easily find transcriptome data they are interested in, such as the experimental conditions in which a gene of interest was differentially expressed in, or all genes that were differentially expressed in an experimental condition. We believe that Mr.Vc database is a comprehensive data repository dedicated to V. cholerae and could be a useful resource for all researchers in related fields. Mr.Vc is available for free at http://bioinfo.life.hust.edu.cn/mrvc .